Emerging Fungal Infections of the Central Nervous System in the Past Decade: A Literature Review - Rita Lino; André Rodrigues Guimarães; Estela Sousa; Mariana Azevedo; Lurdes Santos (MDPI AG, 2024)
Introduction: Invasive fungal infections affecting the central nervous system (CNS) are a major health concern worldwide associated with high mortality rates. Their increased incidence is largely due to an increase in the vulnerable immunocompromised population, changing environmental factors, and development of more accurate diagnostic methods. The aim of this article is to identify fungal causes of CNS infections that are recently emerging or have the potential to become emerging pathogens in the near future, as well as their clinical characteristics, including: Candida auris, Trichosporon spp., Blastomyces spp., Sporothrix spp., Talaromyces marneffei, Lomentospora prolificans, and Scedosporium spp. Methods: A review of the literature in PubMed in the last ten years was conducted to identify central nervous system infections caused by each of these fungi. Results: The review identified 10 cases caused by C. auris, 5 cases by Trichosporon spp., 82 cases by Blastomyces spp., 36 cases by Sporothrix spp., 21 cases by T. marneffei, 22 cases by Lomentospora prolificans, and 42 cases by Scedosporium spp. Discussion: The exact burden of these diseases remains difficult to ascertain, but their apparent rise underscores the urgent need for improved diagnostic, treatment, and management strategies against CNS fungal pathogens to improve outcomes against these life-threatening infections.